N-tangle of the Superposition of Greenberger-Horne-Zeilinger States - Xiu-Li Tu; Ting Zhang; Xian-Ming Wang; Xin-Wei Zha (Institute of Advanced Engineering and Science, 2013)
In the paper, use the n-tangle, as a measure of entanglement to investigate the superposition of Greenberger-Horne-Zeilinger states for even n qubits. The paper show that orthogonal basis with the GHZ state can be divided into two group via SLOCC –invariant. In the same group, an expression for any two superposed state is provided, when the superposition coefficient is real, the n-tangle of superposed state is invariable. Otherwise, In the different group, which can get a different expression if the superposed state come from different group. DOI: http://dx.doi.org/10.11591/telkomnika.v11i6.2718